Application of immobilized titanium dioxide photocatalysts for the degradation of creatinine and phenol, model organic contaminants found in NASA's spacecrafts wastewater streams - Dionysiou, Dionysios Demetriou D.; Antoniou, Maria G. (My University, 2007)
In this project, immobilized titanium dioxide photocatalysis was utilized as a post-treatment technology for the destruction of model organic contaminants found in wastewater streams produced on-board during space exploration. Phenol, a known human carcinogen, and creatinine, a human metabolite found in urine, were the compounds tested in this study. Phenol and creatinine have cyclic structures consisting of six and five member rings, respectively. In addition, creatinine is a methyl guanidine derivative, with almost 40% (w/w) nitrogen. The degradation and carbon mineralization efficiencies of the target contaminants were investigated at different initial concentrations. Their photocatalytic degradation appears to follow pseudo-first-order reaction with phenol giving higher organic carbon reduction rates than creatinine. The presence and position of the functional groups of creatinine (amine, imine and peptide bond) are primarily responsible for the significantly slower mineralization. The degradation of creatinine was also tested at different pHo values. Statistical analysis showed that there is an effect of pH on the treatment of creatinine. Besides the carbon mineralization, the extent of nitrogen mineralization and the mass balance of nitrogen were conducted for three pH values (pHo 3.0, 6.2 and 11.0). Overall, the transformation of nitrogen was low, and the total maximum conversion (<20%) occurred at basic conditions
Keywords: Creatinine; Titanium dioxide; Phenol; Sewage; Carbon